Do You Know I(nformational) T(ext) When You See It? Towards a Workable Definition of Informational Text - O’Connor, Kevin (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Scholars have noted that schools use very little informational text in instruction. This scholarship intersected with the movement to establish common learning standards for the English language arts. One of the results of this confluence is that the Common Core State Standards and, in turn, Ohio’s English language arts learning standards require that a “significant amount” of informational text be used in instruction. Unfortunately, there is confusion about what sort of texts are considered to be informational texts. Practicing English language arts teachers would be greatly assisted by a reliable and understandable definition of informational text. This practitioner’s definition should focus on texts that have the purpose to explain, inform, or persuade.